FORMATION OF LITERARY-AESTHETIC VIEWS OF ERKIN A’ZAM (Scientific journal of the Fergana State University, 2023)
The formation of the writer's literary-aesthetic views is analyzed in this article on the example of memoirs in art journalism. Several memoirs about A. Qahhor, one of the founders of Uzbek realist storytelling, who considered himself a teacher, three memoirs dedicated to A. Mukhtor, who became a great teacher in the field of journalism, art and editing were analyzed.